Retrospective Radiographic Study of Degenerative Joint Disease in Cats: Prevalence Based on Orthogonal Radiographs - Kimura, Taro; Kimura, Sayaka; Okada, Junichi; Suzuki, Sayaka; Kitanaka, Taku (Frontiers in Veterinary Science, 2020)
Feline degenerative joint disease (DJD) has been reported worldwide. Radiographic evidence, including that from single-plane radiographs, has been used for diagnosis in these reports, though orthogonal radiographs are generally required to diagnose DJD. However, more orthogonal radiographs are required for diagnosis. In this study, we investigated how many orthogonal radiographs are necessary to diagnose feline DJD among domestic short-haired cats. We analyzed the data from 101 cats for which the owners requested screening for arthritis. Orthogonal radiographs of appendicular and intervertebral joints were taken from the chest to the caudal side. Radiographs were then reviewed and graded by severity of DJD in each joint. Radiographic evidence of appendicular DJD was detected in 74.26% of 101 cats, of which 40.59% had intervertebral DJD (typically of the lumbosacral joint). Appendicular DJD was most common in elbow joints. Lameness was recognized by an owner of two cats and was diagnosed by a veterinarian in two cats. No obvious pain was detected on palpation in any cats with appendicular osteoarthritis, but lumbosacral DJD was associated with back pain in seven cases. Aging was associated with radiographic evidence of DJD: radiographic evidence of DJD was observed in most older domestic short-haired cats. Most cases without lumbosacral DJD had no obvious symptoms. As the lifespan of cats increases due to better lifestyles, diet, and medical treatment, lumbosacral DJD, which is more likely in older cats, may become an increasingly important clinical problem. In addition, orthogonal radiograph must be taken to make diagnosis for appendicular joint DJD especially hip and stifle joint.